Caregivers’ Burden on Patients with Dementia Having Multiple Chronic Diseases - Jhang KM; Liao GC; Wang WF; Tung YC; Yen SW; Wu HH (Dove Medical Press, 2024)
Kai-Ming Jhang,1,* Guan-Chun Liao,2,* Wen-Fu Wang,1,* Yu-Chun Tung,3,* Shao-Wei Yen,4 Hsin-Hung Wu2,5 1Department of Neurology, Changhua Christian Hospital, Changhua, Taiwan; 2Department of Business Administration, National Changhua University of Education, Changhua, Taiwan; 3Department of Pharmacy, Taichung Veterans General Hospital, Taichung, Taiwan; 4Department of Information Management, National Changhua University of Education, Changhua, Taiwan; 5Faculty of Education, State University of Malang, Malang, East Java, Indonesia*These authors contributed equally to this workCorrespondence: Hsin-Hung Wu, Email hhwu@cc.ncue.edu.twPurpose: This study aimed to find the caregiving burden level for patients with dementia who had multiple chronic diseases by simultaneously considering both patient and caregiver factors.Participants and Methods: A cross-sectional study with 284 patients with dementia having multiple chronic diseases managed by the dementia collaborative care team at Changhua Christian Hospital in Taiwan was conducted. The input variables were from patients, such as age, gender, mood symptoms, and behavioral and psychological symptoms, and caregivers, including age, relation to the patient, caregiver's mood, and caregiving burden. The Apriori algorithm was employed to determine the association between patient and caregiver factors and different caregiving burden levels by setting up the minimum support of 1% and confidence of 90% along with lift > 1.Results: When caring for patients with dementia, twenty scenarios were found for caregivers with a severe burden. In addition, 1936 scenarios were related to caregivers with a moderate-to-severe burden. Specifically, there were eight scenarios for patients with three chronic diseases which could be further categorized into five general rules. Two hundred and fifty scenarios belonging to patients with two chronic diseases could be classified into 16 different combinations from eight chronic diseases of the database.Conclusion: Caregiver's mood, patients with mild dementia, and patients aged 75- 84 years were associated with a severe caregiving burden. College and above education of the caregiver, the patient aged 85 years or more, and at least one of caregiver's moods were the variables to result in a moderate-to-severe burden for caregivers caring for patients with three multiple chronic diseases. Moreover, college and above education of the caregiver, mood symptom, age of the caregiver, and age of the patient were important variables for caregivers who had a moderate-to-severe burden taking care of patients with two chronic diseases.Keywords: patients with dementia, multiple chronic diseases, behavior and psychological symptoms of dementia, mood symptom, caregiving burden, dementia collaborative care team, apriori algorithm